Trajetória ideal do neuroendoscópio no acesso ao pavimento do terceiro ventrículo - Joana Catarina Borges de Sousa (2024)
Background & Aim: Endoscopic Third Ventriculostomy (ETV) is a surgical procedure used to treat hydrocephalus, a condition characterized by an abnormal accumulation of cerebrospinal fluid in the ventricles of the brain. This study seeks to establish a standardized and safe approach for Free-Hand ETV by defining a new trajectory and entry entry point to reach the third ventricle pavement. This procedure is used in settings where the equipment for fixed or robotic-assisted surgery is unavailable or in specific emergency scenarios, including acute hydrocephalus or a sudden worsening of the condition that poses an immediate risk to the life of the patient. Methods: 187 MRIs were analyzed, of which 30 presented hydrocephalus. A pathway crossing the cranial bone, foramen of Monro, and tuber cinereum was outlined. Measurements included the entry point location relative to cranial sutures, pathway angulations, depth, and distances to key anatomical landmarks. Comparisons between hydrocephalic and non-hydrocephalic patients were made, with assessments of variations linked to age, sex, and Evan's index. Results: There are significant differences in various surgical parameters between hydrocephalic and non-hydrocephalic patients. Hydrocephalic patients had greater mean depth (93.520±7.228 mm), coronal plane angulation (10.982°±6.119°), and mean distance from the entry point to the sagittal suture (18.957±8.608 mm), but a smaller median distance to the superior frontal sulcus (7.00 mm, IQR=11.50 mm). The remaining variables showed no significant differences, with a mean of 2.549°±3.576° for the sagittal plane angulation, a mean distance to the precentral sulcus of 19.93±7.955 mm and a median distance to the coronal suture of 10.55 mm (IQR=11.00 mm). Conclusions: By delineating a novel pathway and entry point interval, the study offers a promising path for the urgent care of hydrocephalus. The new entry point is strategically positioned near the coronal and sagittal sutures, while ensuring a safe distance from the precentral and superior frontal sulci. This approach might be useful to improve surgical precision and patient outcomes in the management of hydrocephalus.